Study on the remineralization of demineralized enamel surfaces with glycine-guided carboxymethyl chitosan/amorphous calcium phosphate - GUO Honglei; ZHANG Kai; ZHANG Xu (口腔疾病防治, 2022)
Objective To explore effect on the remineralization of demineralized enamel surfaces with glycine-guided carboxymethyl chitosan (CMC)/amorphous calcium phosphate (ACP). Methods Remineralized solultion at different stages were prepared: ①reactive CMC/ACP (CMC/ACP nanoparticles treated with NaClO), ②reactive CMC/ACP+glycine; transmission electron microscopy was used to detect the morphology of the remineralized solution particles. Twenty teeth were randomly divided into two groups: group A and group B. Reactive CMC/ACP was applied to the enamel surface of group A and group B was treated with reactive CMC/ACP remineralization solution containing glycine. Scanning electron microscopy was used to detect the enamel surface morphology before and after remineralization, and nanoindentation was used to detect the mechanical strength (including nanoindentation depth, hardness and elastic modulus) of the enamel surface. Results Under a transmission electron microscope, the particles in the reactive CMC/ACP remineralization solution were smooth, and the increase in particle size was approximately 100-300 nm. After the addition of glycine, the particles in the reactive CMC/ACP remineralization solution particles showed a linear ordered arrangement, and microcrystals were formed in the solution 15 min later, with a crystal length of approximately 5-15 μm. Remineralization in group A was granular and heterogeneous. In group B, the crystal morphology of the demineralized enamel was homogeneous and ordered, similar to that of natural enamel. The nanoindentation depth of group B after remineralization was smaller than that of group A, and it was closest to that of natural enamel, there was no significant difference between group B and natural enamel in terms of the hardness and elastic modulus of the enamel surface after remineralization. Conclusion CMC/ACP nanoparticles treated with NaClO can rapidly and specifically form directional and ordered remineralization on the enamel surface of a model of glycine-guided rapid remineralization of enamel caries. The surface structure of remineralized enamel is similar to that of natural enamel in terms of nanoindentation depth, hardness and elastic modulus.